Factors associated with access to physical rehabilitation for victims of traffic accidents - Kelienny de Meneses Sousa; Wagner Ivan Fonsêca de Oliveira; Emanuel Augusto Alves; Zenewton André da Silva Gama
ABSTRACT OBJECTIVE Evaluate the level of access to physical rehabilitation for survivors of traffic accidents and the associated factors. METHODS A cross-sectional study performed in Natal, Northeastern Brazil, through a telephone survey of 155 victims of traffic accidents admitted to an emergency hospital between January and August of 2013, with a diagnosis of fracture, traumatic brain injury or amputation. Participants were identified in the database of the reference hospital for care of traffic accident victims. We calculated point estimates and confidence interval (95%CI) for the frequency of subjects who had access, in addition to multivariate analysis (logistic regression) between access (dependent variable) and sociodemographic, clinical, and assistance variables. RESULTS Among the 155 respondents, the majority were adolescents and adults between 15-29 years of age (47.7%), men (82.6%), education up to high school (92.3%), income of up to two minimum wages (78.0%) and bikers (75.5%). Although 85.8% of traffic accident survivors reported the need for physical rehabilitation, there was little access (51.6%; 95%CI 43.7-59.4) and a delay to start the physical rehabilitation (average = 67 days). We classified factors associated with access to physical rehabilitation as: (i) unmodifiable individuals in the short term - family income greater than two minimum wages (OR = 3.7), informal worker (OR = 0.11) or unemployed (OR = 0.15) and possession of a private health care plan (OR = 0.07); and (ii) assistance modifiable by service management - written referral for physical rehabilitation (OR = 27.5) and perceived need of physical rehabilitation (OR = 10). CONCLUSIONS This study found a low and slow access to physical rehabilitation for individuals potentially in need. The associated factors were the organizational processes of health care (health information and referral) and social determinants (income, occupation and private health care plan).